2024
DOI: 10.1126/sciadv.adj0341
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of defense systems in phage-resistant strains of Pseudomonas aeruginosa

Ana Rita Costa,
Daan F. van den Berg,
Jelger Q. Esser
et al.

Abstract: Prokaryotes encode multiple distinct anti-phage defense systems in their genomes. However, the impact of carrying a multitude of defense systems on phage resistance remains unclear, especially in a clinical context. Using a collection of antibiotic-resistant clinical strains of Pseudomonas aeruginosa and a broad panel of phages, we demonstrate that defense systems contribute substantially to defining phage host range and that overall phage resistance scales with the number of defense sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 92 publications
0
2
1
Order By: Relevance
“…Our investigation into bacterial defense systems yielded unexpected results, as we found no evidence linking these systems to lytic phage susceptibility or resistance. Our findings are surprising given previous studies indicating the opposite, where defense mechanisms were shown to protect from phage infection 26,43,44 , or a recent study indicating an accumulation of defense systems in phage-resistant Pa strains 45 .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our investigation into bacterial defense systems yielded unexpected results, as we found no evidence linking these systems to lytic phage susceptibility or resistance. Our findings are surprising given previous studies indicating the opposite, where defense mechanisms were shown to protect from phage infection 26,43,44 , or a recent study indicating an accumulation of defense systems in phage-resistant Pa strains 45 .…”
Section: Discussioncontrasting
confidence: 99%
“…Our experiments demonstrate that bacterial defense systems do not influence initial lytic phage infection, which determines host range. Different approaches or experiments exploring the relationship and evolution between phages and hosts over an extended period, particularly those focusing on the development of phage resistance, may yield different outcomes, shown by a recent study suggested an accumulation of defense systems in phage-resistant Pa strains 45.…”
mentioning
confidence: 99%
“…No CRISPR-Cas or TA systems were identified in the analysis, only RM, AMP-ligating, and unidentified systems. Overall, the phage-defense system carriage rate of H. salinarum is low compared to bacteria, which can carry upwards of 15 defense systems [62].…”
Section: Discussionmentioning
confidence: 97%